The Greatest Popular Songs of Xmas, 1979 (and the KCPR trip to the North Pole) - Christy Kuehler:::::::::; Brian Hackney:::::::::; Al Yankovic:::::::::; Jerry Peek::::::::: (1979)
Recording of program produced by Cal Poly's student radio station KCPR, featuring then-Cal Poly student and KCPR DJ, Weird Al Yankovic. [00:24:04] Brian Hackney talks about Jimmy Boyd [00:24:10] Jimmy Boyd - I Saw Mommy Kissing Santa Claus [00:27:19] Eartha Kitt - Santa Baby [00:30:51] Ray Conniff - Winter Wonderland [00:33:46] Bing Crosby - Do You Hear What I Hear [00:36:37] Commercials cut out, Brian Hackney discusses Spike Jones [00:37:49] Spike Jones - All I Want For Christmas is my Two Front Teeth [00:41:11] Alvin and the Chipmunks - Christmas Don't Be Late [00:43:27] Muppets - The Twelve Days of Christmas [00:47:35] Tom Lehrer - A Christmas Carol [00:49:46] Brian Hackney talks about Brenda Lee [00:50:12] Brenda Lee - Rockin' Around the Christmas Tree [00:52:10] Brian Hackney talks about Elvis and the Rockabilly genre [00:52:52] Jingle Bell Rock [00:55:02] Jose Feliciano - Feliz Navidad [00:58:25] The Carpenters - Merry Christmas Darling [01:02:05] Gene Autry - Rudolph the Red-Nosed Reindeer [01:05:43] Bing Crosby - I'm Dreaming of a White Christmas [01:08:50] Brian Hackney thanks KCPR employees and ends program